Double-Row Repair Technique for Bursal-Sided Partial-Thickness Rotator Cuff Tears - Salem, Hytham (Arthrosc Tech, 2018)
Rotator cuff pathology is a common cause of shoulder pain in the athletic and general population. Partial-thickness rotator cuff tears (PTRCT) are commonly encountered and can be bursal-sided, articular-sided, or intratendinous. Various techniques exist for the repair of bursal-sided PTRCTs. The 2 main distinctions when addressing these lesions include tear completion versus preservation of the intact fibers, and single- versus double-row suture anchor fixation. We present our method for addressing bursal-sided PTRCTs using an in situ repair technique with double-row suture anchors.